(3ZfjI GdWdGH aj eYQaI GdQei HGdfTGHs - (3YdGA GdOjf WjHZG GdHcdeTi GdCTQ ai GdjhfGfis; (3WjHhZG GdCTQaj , WjHhZG GdGTQaj GdHWdeTj GdjhfGfj, YdGA GdOjf,J (B770 (3g` s ((3eMeO Hf Ydi GdCfUGQi s)
(3ChdgG (B:s
(3CeG HYO paEf Gddg JYGdi MjK aQV YdjfG Qei GdfTGH GdLRjd GdKhGH s
(3BNQgG (B:s
(3aGLYd GdOjf cgac , GdYOd Sjac , JfLM ef cd Sh hJRaQ Hcd eQLh s
(3GfXQ fSNI CNQi HQbe (B5 (3ai gPJ GdagQS HYfhGf (B" (3HZjI GdeQGei (B"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B46s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B135 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B24 s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs